(untitled) (SAARC Journal of Agriculture, 2015)
Field experiments were conducted at the Central Research Station of Bangladesh Agricultural Research Institute (BARI) for three consecutive years (2011-12, 2012-13 and 2013-14) to study the comparative agronomic performance and economic return of different cropping sequences for increasing cropping intensity and productivity. Three cropping patterns (CP1 - Transplanted Aman rice (var:Binadhan-7) Mustard (var:BARISarisha-14) Boro rice (var:BRRIdhan-28) Transplanted Aus rice (var:Parija), CP2 - T. aman rice Potato (var:Diamont) Boro rice T. aus rice and CP3 - T. aman rice Mustard (var:BARISarisha-15) Mungbean (var:BARIMung-6) T. aus rice) are based on four crops; and one cropping pattern (CP4 = T. aman rice Fallow Boro rice Fallow) with two rice crops as control were tested. Four crops can be grown successfully one after another in sequence in all the three cropping patterns tested. On an average organic matter 3.56, 4.70, 3.58 and 2 t ha-1 were added to soil in CP1, CP2, CP3 and CP4 by incorporation of biomass of respective crops. The highest rice equivalent yield (REY) 34.10, 34.02 and 33.36 t ha-1 was obtained from the cropping pattern CP2 in 2011-12, 2012-13 and 2013-14, respectively and it was followed by CP1 and CP3. The highest average gross return (Tk.5,00,469 ha-1) and net return (Tk. 2,63,773 ha-1) were obtained from CP2 and it was followed by CP3 but the highest average B:C ratio (2.89) was obtained from the cropping pattern CP3 followed by CP2 (2.11) due to lower cost of production than in the former one. Four crops based patterns can be recommended for higher productivity, soil enrichment & economic benefit besides creating more employment opportunity. SAARC J. Agri., 13(1): 135-147 (2015)